Literature Review: The Influence of Work Appraisal on Employee Performance in a Company - Milna Ristiawansyah (West Science Business and Management, 2023)
Employees are important assets for the company, because the roles and functions of employees aim to help expedite productivity and maximize performance and use time effectively and efficiently. This study aims to determine the effect of work assessment to performance employee in something company and also aim for review the effect of performance appraisal on employees in an organization or company. This study uses the Literature Review method or literature review. Performance appraisal is also known as a performance review, performance evaluation, or employee appraisal which aims to increase employee productivity in a company. The purpose of performance appraisal is as follows: (1) As a basis for decision making. (2) As a basis foresee or estimate performance with method correlate results test with rating result performance. (3) Give bait come back to employee, so that evaluation performance can function as a vehicle for self-development and employee career development. (4) Performance appraisal can help determine the objectives of the training program. (5) Performance appraisal can help diagnose organizational problems. The function of performance appraisal is to encourage performance improvement. Performance appraisal is used as a means of communicating with employees regarding how they work and what means are needed to change behavior and attitudes, as well as a means of developing their skills and knowledge. Good job evaluation is very closely used to evaluate employee performance in accordance with the components of the job evaluation being assessed, for example, attendance, honesty, responsibility, work ability, loyalty, obedience, leadership and cooperation, as well as employee initiatives or ideas. Good, effective and clear performance appraisals will make employees more motivated to continue working diligently, and good work appraisals will have an impact on the enthusiasm of employees in doing work.